Pluralizm metafizyczny, czyli o religii jako tworzywie dzieła artystycznego - Jocz, Artur (Polskie Towarzystwo Religioznawcze, 2010)
Artur Jocz – METAPHYSICAL PLURALISM, OR RELIGION AS THE MATERIAL OF THE WORK OF ART The fundamental aim of these reflections is not a detailed reconstruction of the evolution of European metaphysics. The origins and development of this metaphysics will only be mentioned briefly. The attention will be focused mainly on the act of observation of reality in which there is no single metaphysical vision since it was replaced by metaphysical pluralism. For the use of these considerations it is enough to discuss only one element of this colourful reality. In other words, the aim of this article is to consider the migration of some selected conceptual categories that original-ly were components of religious-philosophical conceptions. These conceptions came into being as a result of metaphysical pluralism. Due to this process, these categories became the material of works of art. Thus, it will be another example of relations between religious and artistic activity. The diver-sity of this phenomenon will be illustrated by two examples taken from literature and film.